Bioremediation of Hexavalent Chromium in Potassium Dichromate Solution by Botrytis aclada fres and Chrysonilia sitophila - Adeniran, Olufemi; Shugaba, Aliyu (International Journal of Biotechnology for Wellness Industries, 2016)
Bioremediation of hexavalent chromium, Cr(VI) by Botrytis aclada fres and Chrysonilia sitophila was studied. The organisms were isolated from decaying onion bulb and apple fruit respectively, purified in Potato Dextrose Agar, and grown for 144 hours in solutions of potassium dichromate of concentrations ranging from 5-20 mg/l at 400C. Effective reduction of Cr(VI) was observed at 5-20 mg/l compared to 25 mg/l dichromate treatments in both organisms. The results showed significant decrease (P < 0.05) in biomass concentration in the two fungi used with increasing concentration of the dichromate treatment (5-25 mg/l). Significant increase (P < 0.05) in residual glucose concentration was also observed in the culture media with increase in concentration of the dichromate treatment. However, at 20 mg/l dichromate treatment, Cr(IV) concentration, 1.36 ± 0.02 and 1.71 ± 0.03 (P < 0.05) were revealed in the culture media of B. aclada fres and C. sitophila respectively. Also, 0.71 ± 0.03 and 0.94 ± 0.03 Cr(IV) concentration (P < 0.05) were observed in the fungal mycelia at 20 mg/l dichromate treatment in B. aclada fres and C. sitophila respectively. After 144 hours of growth, Cr(VI) reduction of 89.65% in B. aclada fres and 86.75% in C. sitophila at 20 mg/l dichromate treatment were revealed. This investigation suggests that the two fungi adopted a process of reduction to tolerate the toxicity of hexavalent chromium. The results indicate the potentials of the fungi in bioremediation particularly in the treatment of waste water containing hexavalent chromium.